Propriedades vibracionais do dipeptídeo L,L-difenilalanina sob condições extremas de temperatura e pressão - Silva Filho, José Gadelha da (2017)
In this thesis, we investigated the stability of the aromatic dipeptide L,L-diphenylalanine under extreme conditions of temperature and pressure. Firstly, the crystalline phase of the dipeptide was confirmed by Rietveld analysis. During this refinement, the instrumental and structural parameters were refined and a good fit was found between observed and calculated peak positions. Next, we have studied the hexagonal phase of this dipeptide under both low- and high-temperature conditions, using nondestructive Raman spectroscopy and infrared techniques. The experimental bands have been assigned on the basis of first principles calculations. Infrared spectra were taken of the sample as the sample was cooled up to 160 K, whereas the Raman spectra were collected at even lower temperatures, around 20 K. Our vibrational data indicate a structural stability in this temperature range. On the other hand, Raman spectra recorded in the Y(XX)Y and Y(ZZ)Y polarization scheme for L,L -diphenylalanine provides evidence of a phase transition at high temperatures (≈ 390 K). The major changes occurring in the Raman spectrum of L,L-diphenylalanine involve the bands in the low-wavenumber region (≤ 200 cm-1), accompanied by the softening of the amide I peak and the broadening of bands associated with the vibrational motions of the aromatic radicals. This phase transition was confirmed by thermoanalytical methods and X-ray diffraction experiments. The XRD patterns were collected as the sample was cooled up to 83 K (≈ -190 ºC) and heated to 473 K (≈ 200 ºC). The hexagonal phase of the L,L-diphenylalanine is stable until the limit of 393-403 K is reached. Increasing the temperature from 403 to 413 K induces significant changes in the observed crystalline phase. Finally, we report a high-pressure study (0.0-7.4 GPa) of L,L-diphenylalanine crystals using Raman spectroscopy. The application of high-pressure leads to considerable modifications in the vibrational bands, mainly between 3.9 GPa and 4.6 GPa. This includes the disappearance of Raman bands in the spectral region associated with the lattice mode vibrations and changes in the relative intensities of some internal-mode lines. During decompression, from 7.4 GPa, the reversion to the hexagonal phase indicates that there is little or no hysteresis between 2.7 and 0.7 GPa.